2021
DOI: 10.1158/2159-8290.cd-20-0119
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis in Cancer-Associated Fibroblasts Is Dependent on CaMKK2/ARHGEF2 Signaling and Functions to Support Tumor and Stromal Cell Fitness

Abstract: Although pancreatic ductal adenocarcinoma (PDAC) cells are exposed to a nutrient-depleted tumor microenvironment, they can acquire nutrients via macropinocytosis, an endocytic form of protein scavenging that functions to support cancer metabolism. Here, we provide evidence that macropinocytosis is also operational in the pancreatic tumor stroma. We find that glutamine deficiency triggers macropinocytic uptake in pancreatic cancer–associated fibroblasts (CAF). Mechanistically, we decipher that stromal macropino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…Zhang et al have reported that glutamine deficiency triggers macropinocytic nutrient uptake in pancreatic CAFs by the enhancement of cytosolic Ca2 + and CaMKK2-AMPK signaling. Herein, macropinocytosis contributes to intracellular and extracellular amino acid pools that sustain CAF fitness and promote tumor cell survival [62].…”
Section: Functions Of Cafsmentioning
confidence: 99%
“…Zhang et al have reported that glutamine deficiency triggers macropinocytic nutrient uptake in pancreatic CAFs by the enhancement of cytosolic Ca2 + and CaMKK2-AMPK signaling. Herein, macropinocytosis contributes to intracellular and extracellular amino acid pools that sustain CAF fitness and promote tumor cell survival [62].…”
Section: Functions Of Cafsmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is defined in part by an exuberant stromal reaction, including abundant cancer-associated fibroblasts (CAFs) (1)(2)(3)(4). Diverse tumorsupportive functions have been ascribed to PDAC CAFs, including metabolic roles whereby nutrient transfer from CAFs to neighboring pancreatic cancer cells facilitates proliferation within a nutrient-poor microenvironment (5)(6)(7)(8)(9). In addition, PDAC CAFs produce cytokines and chemokines associated with immune suppression (10)(11)(12)(13), and CAF ablation in mice fosters efficacy of immune checkpoint inhibitors which are otherwise ineffective in PDAC (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…By affording access to diverse sources of nutrients, macropinocytosis is emerging as a metabolic adaptation that contributes to multiple fitness determinants. There is also evidence to suggest that macropinocytosis is sensitive to nutrient availability [16,24,25]. These important observations invoke the idea that tumor cells can selectively tune macropinocytic activity to modulate nutrient scavenging according to their metabolic needs, further reinforcing the connection between macropinocytosis and metabolic fitness.…”
Section: Nucleotidesmentioning
confidence: 93%